PENGGUNAAN PENDEKATAN KETERAMPILAN PROSES UNTUK MENINGKATKAN HASIL BELAJAR IPA DI KELAS V SD NEGERI 02 MANGGILANG - Ermitati, Ermitati (EDUTECH CONSULTANT, 2018)
This research is a classroom action research using qualitative and quantitative approach. Research data in the form of information about process and data result of action obtained from result of observation, test result and discussion. Sources of data were obtained from the approach of learning process skill approach in science lesson. Research subjects consisted of teachers and students of class V SD Negeri 02 Manggilang which amounted to 20 people. The research procedure is done: planning, action, observation and reflection. The results of the research In the first cycle obtained the results of the implementation in view of the aspects of teacher meetings I 75%, meeting II 78.5% and student aspects meeting 67.8%, meeting II 75% while the results of implementation in cycle II seen from aspects of teachers 89, 2% and student aspect 92,8%. Therefore, it is suggested that teachers can implement the learning process using the Process Skills approach.